Silver nanoparticles selectively induce human oncogenic γ-herpesvirus-related cancer cell death through reactivating viral lytic replication - Wan, Chunlei; Tai, Jiahui; Zhang, Jie; Guo, Yi; Zhu, Qing; Ling, Ding; Gu, Feng; Gan, Jin; Zhu, Caixia; Wang, Yuyan; Liu, Sijin; Wei, Fang; et al. (Cell death & disease, 2019)
Silver nanoparticle (nAg), which is one of the most common manufactured nanomaterials, has a wide range of biomedical applications. The human oncogenic γ-herpesviruses, Kaposi’s sarcoma-associated herpesvirus (KSHV) and Epstein–Barr Virus (EBV), are etiologically linked to many malignancies. Currently, there are no efficient or specific treatments for these types of tumors, and most patients die because of resistance to conventional cytotoxic chemotherapy. Despite nAg having antitumor and antiviral activities, its effects on oncogenic herpesvirus-related cancer cells remain largely unknown. Here, we reveal that nAg presents higher cytotoxicity against KSHV- or EBV-latently infected cells via reactivating viral lytic replication, which relies on the induction of reactive oxygen species (ROS) generation and autophagy. Moreover, nAg blocks KSHV primary infection by directly destroying virion particles, as well as effectively inhibits colony formation and moderately represses the growth of KSHV-associated tumors in xenograft mouse model. Taken together, these results demonstrate the therapeutic potential of nAg for use in the antiviral infection and treatment of oncogenic herpesvirus-related cancers.